Peningkatan Kesadaran Pelaku Usaha Olahan Ayam Terhadap Sertifikasi Halal Melalui Sosialisasi di Wilayah Sindangsari - Risa Anggraini; Aulya Aginia Priyono; Destia Bisma Nurfatimah; Munjiatus Sholihat; Sifa Aulia; Riski Andrian Jasmi (Jurnal Pengabdian kepada Masyarakat Radisi, 2025)
Micro-scale chicken processing entrepreneurs in Sindangsari Village, Serang Regency, have limited understanding of the importance of halal certification. This certification plays a vital role in building Muslim consumer trust, expanding market access, and ensuring compliance with Sharia principles across the production chain. This community service aimed to enhance halal literacy through educational socialization explaining the concept, benefits, and procedures of halal certification in accordance with national regulations, particularly Law No. 33 of 2014 concerning Halal Product Assurance. A quantitative approach with a pre-test and post-test design without a control group was applied to three purposively selected entrepreneurs. Data were collected using structured questionnaires before and after the intervention. The results indicated significant improvement in understanding the definition of halal food (100%), examples of halal food (99%), and the purpose of halal labeling (67%). Moderate improvement occurred in identifying haram ingredients (20%) and interpreting the halal logo (25%) since participants had prior basic knowledge. These findings confirm that educational outreach integrating Sharia values and regulatory frameworks effectively enhances halal awareness among micro-entrepreneurs. Continuous mentoring is necessary to ensure that participants not only comprehend but also implement halal standards as part of sustainable and competitive business practices.